E-Finance An Evaluation Of Its Application In The Malaysia Corporate Sector - Teck, Wong Kong (2004)
E-Finance especially online banking has reshaped the financial landscape around the world including Malaysia in recent years. E-finance is also dramatically changing the structure and nature of markets for financial services. This studies review development and analysis their implications for consumers, industries, goverments and financial services provider.